The effects of diltiazem in renal transplantation patients treated with cyclosporine A() - Xue, Wujun (Editorial Department of Journal of Biomedical Research, 2010)
OBJECTIVE: To investigate the effects of diltiazem and cyclosporine A (CsA) combination therapy on protecting the kidney, promoting graft functioning and improving post-transplanted kidney recovery. METHODS: The blood concentrations of CsA, the condition of the post-transplant kidney, the rate of acute rejection (AR), as well as hepatic and renal toxicity in 636 cases of renal transplant recipients were determined after being treated by CsA, with or without diltiazem. RESULTS: Compared with the control group which received CsA, mycophenolate mofetil (MMF) and prednisolone (Pred) but lacked diltiazem, the group receiving these agents together with diltiazem required reduced dosage of CsA (P < 0.01), while blood concentrations of CsA were significantly increased (P < 0.01); the recovery time of graft function was reduced from (6.2±1.5) d to (3.9±1.4) d (P < 0.01), and the rate of AR was decreased from 13.2% to 7.9% (P < 0.01). CONCLUSION: In renal transplantation patients treated with CsA and diltiazem, blood concentrations of CsA were increased while the dosage was decreased. This efficient combination therapy reduced patients' economic burden, at the same time retained kidney function, promoted graft function recovery and decreased hepatic and renal toxicity and the rate of AR.